LITERASI MEDIA SOSIAL DALAM MENANGKAL BERITA "HOAX" DIKALANGAN MASYARAKAT: STUDI PADA MAHASISWA HEAVY USER LINE TODAY DI UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Dede Saputra (2020)
Social media currently has a lot of information elements that are still regarded as facts that are not necessarily true, such as hoax news. On the other hand the role of media liteation is really needed in providing understanding to the public so that it does not cause behavioral changes in consuming media. Line social media can also cause hoax news because line social media is still considered news that is uncertain. Therefore, this study aims to determine how media literacy can ward off hoax news among the public, especially students. The research method used is a qualitative phenomenological approach with the foundation of media literacy theory in the Line Messenger social media. The results of this study will be associated with looking at the concepts and theories that the author uses to get the desired results, namely how students' understanding at UPN "Veterans" Jakarta in understanding the importance of media literacy in using social media to ward off hoax news that is circulating in social media today, where according to Baran and Dennis (2010), which explains that media literacy as a series of media literacy activities that is media literacy movement is designed to increase individual control over the media they use to send and receive messages, which the concept of this research is social media, hoaxes and an understanding of the importance of literacy can answer the questions in this study that the six informants have understood the importance of media literacy in using social media at this time. In order to avoid the impact of media information which can sometimes mislead media users in using social media in other words such as hoax news issues spread by social media at this time. The conclusion of this study is the importance of awareness to understand and apply media literacy in using social media, so that we as social media users are more critical and intelligent in accepting information provided by social media.